Impact of the Cross-Curricular Education Program on Food Intake, Physical Activity, and Body Mass Index of School Children in a Local Community in Northern Serbia - Sanja Šumonja (MDPI AG, 2021)
Introduction: The trends in the state of nutrition and physical activity of school-age children in Serbia impose a need to create and evaluate programs to improve their nutrition and physical activity. The purpose of this study was to evaluate the impact of the cross-curricular nutrition and physical activity education program (NPAEP) on food intake, physical activity, and body mass index in first–fourth-grade primary school children. Material and methods: The study used an experimental pre-test (t1) post-test (t2) design. The sample included 167 participants in t1 and 178 in t2. The differences in food intake, physical activity, and body mass index before and after implementation of the cross-curricular nutrition and physical activity education program were analyzed using the Mann–Whitney U test, the Chi-squared test, and the Wilcoxon signed-rank test. Values p < 0.05 were considered statistically significant. Results: Fruit (t1 = 0.70 ± 0.55; t2 = 1.26 ± 0.65; p < 0.001) and dairy intake (t1 = 1.52; t2 = 1.79; p = 0.005) significantly increased in the intervention group. A significant reduction in time spent watching television (t1 = 78.0; t2 = 56.7; p = 0.005) and playing on the computer (t1 = 32.3; t2 = 25.8; p = 0.047) was achieved in the intervention group. Time spent in organized sports activities significantly increased only in the intervention group (t1 = 21.9; t2 = 30.5; p = 0.046). Body mass index did not change significantly in the intervention group after the implementation of the NPAEP. Conclusions: The nutrition and physical activity education program contributed to an increase in fruit and dairy intake and time spent in intense physical activities and a reduction in screen time. The presented results justify the application of the NPAEP in improving the nutrition and physical activity of first–fourth-grade primary school children.